Nexus between women’s financial empowerment, and digital financial literacy: The case of green microfinance in Tunisia - Miled, Kamel Bel Hadj; Landolsi, Monia (Edelweiss Applied Science and Technology, 2024)
This study examines the relationship between financial literacy (FL) Green Microfinance (GM) and Women’s Empowerment (WE). Alongside its economic and social implications, microfinance has adapted to address expanding demands by integrating environmental factors, resulting in the emergence of GM and WE. The connection between the empowerment of women and green microfinance is partly influenced by their level of FL. The findings highlight the significance of prioritizing financial strategies in Tunisia to promote policies that support women’s empowerment, to fight poverty and environmental sustainability.